Anti-inflammatory Role of Galectin-8 During Trypanosoma cruzi Chronic Infection - Bertelli, Adriano (2020)
Galectins are animal lectins with high affinity for β-galactosides that drive the immune response through several mechanisms. In particular, the role of galectin-8 (Gal-8) in inflammation remains controversial. To analyze its role in a chronic inflammatory environment, we studied a murine model of Trypanosoma cruzi infection. The parasite induces alterations that lead to the development of chronic cardiomyopathy and/or megaviscera in 30% of infected patients. The strong cardiac inflammation along with fibrosis leads to cardiomyopathy, the most relevant consequence of Chagas disease. By analyzing infected wild-type (iWT) and Gal-8-deficient (iGal-8KO) C57BL/6J mice at the chronic phase (4–5 months post-infection), we observed that the lack of Gal-8 favored a generalized increase in heart, skeletal muscle, and liver inflammation associated with extensive fibrosis, unrelated to tissue parasite loads. Remarkably, increased frequencies of neutrophils and macrophages were observed within cardiac iGal-8KO tissue by flow cytometry. It has been proposed that Gal-8, as well as other galectins, induces the surface expression of the inner molecule phosphatidylserine on activated neutrophils, which serves as an “eat-me” signal for macrophages, favoring viable neutrophil removal and tissue injury protection, a process known as preaparesis. We found that the increased neutrophil rates could be associated with the absence of Gal-8-dependent preaparesis, leading to a diminished neutrophil-clearing capability in macrophages. Thus, our results support that Gal-8 exerts an anti-inflammatory role in chronic T. cruzi infection.